The Issue of Integrative Organization of Native Language and Literature Lessons in Primary Grades - qizi, Avezova Marjona Hasan (Research Parks Publishers, 2023)
In this article, the issue of integrative organization of elementary school mother tongue and reading literacy lessons is analyzed scientifically and theoretically.